2019
DOI: 10.1155/2019/3658125
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Durability Characteristics of Latex‐Modified Fiber‐Reinforced Segment Concrete as a Function of Microsilica Content

Abstract: is study evaluated the performance of latex-modified fiber-reinforced concrete (RC) segments as a function of the substitution level of microsilica and type of reinforced fiber, to address the problem of corrosion of steel segments and steel-reinforced fiber segments, which are commonly used to shield tunnel-boring machine (TBM) tunnels in urban spaces. Our study compared macro synthetic, steel, and hybrid (macro synthetic fiber + polypropylene fiber) reinforcing fibers. e substitution levels of microsilica us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The comparison of the findings with those of other studies [ 30 , 31 , 38 ] confirms that both silica fume and fibers significantly increase the load capacity of the PCP slab and, as a result, reduce its thickness. However, this study showed that the effect of reduction depends not only on the concrete mechanical characteristics, base type and joint type but also on the design method.…”
Section: Analysis and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The comparison of the findings with those of other studies [ 30 , 31 , 38 ] confirms that both silica fume and fibers significantly increase the load capacity of the PCP slab and, as a result, reduce its thickness. However, this study showed that the effect of reduction depends not only on the concrete mechanical characteristics, base type and joint type but also on the design method.…”
Section: Analysis and Discussionsupporting
confidence: 80%
“…Higher content of fibers also significantly influenced the total deformations, which are important for the serviceability limit state. In general, an improvement of concrete characteristics leads to a reduction in the thickness of concrete slabs [ 30 ]. Parker [ 31 ] found that fiber reinforced concrete reduces the thickness of the thin concrete layer by 30% to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Wang [69] increased the compressive strength of LWC by 23% by using lightweight shale aggregate. Lee and Song [70] found that adding 1% steel fiber to LWC utilizing cellular expanded shale aggregate increased the compressive strength by 37%. In this investigation, steel fiber added to coconut shell concrete enhanced the compressive strength from 15% to 39%.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The inclusion of SBR latex enhances the workability, compressive strength, and flexural strength of pervious concrete, as well as the split tensile strength [18]. The addition of latex to concrete enhanced water permeability resistance due to the creation of a latex layer on the concrete [19] and reduced water absorption in concrete [20]. The incorporation of styrene-butadiene rubber (SBR) latex into light-weight aggregate concrete reduced the water content of the concrete, and it was discovered that latex reduces the penetration of chloride ions [21].…”
Section: Introductionmentioning
confidence: 99%